PEREMPUAN DALAM KEBIJAKAN: KAJIAN TERHADAP DISKRIMINASI GENDER DALAM KEBIJAKAN - Desti Widiani; Layyin Mahfiana (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
This research’s aim is to study woman discrimination in Indonesian policy especially in Surakarta region. This study uses law sociology approach with both observation and interview as method to gather the data, while for the data analysis, it utilizes Miles & Huberman’s Interactive model that include data display, drawing conclution, and verifying. The result shows that Sukoharjo authority empowers woman through policy by establishing Dinas Pengendalian Penduduk, Keluarga Berencana dan Pemberdayaan Perempuan dan Perlindungan Anak. Eventhought this special taskforce is established, the authority still facing drawbacks and one of them is the lack of stakeholders’ participation which lead to its slow development.